2017
DOI: 10.3390/aerospace4030041
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ability of the DDES Turbulence Modeling Approach to Simulate the Wake of a Bluff Body

Abstract: Abstract:A detailed numerical investigation of the flow behind a square cylinder at a Reynolds number of 21,400 is conducted to assess the ability of the delayed detached-eddy simulation (DDES) modeling approach to accurately predict the velocity recovery in the wake of a bluff body. Three-dimensional unsteady Reynolds-averaged Navier-Stokes (URANS) and DDES simulations making use of the Spalart-Allmaras turbulence model are carried out using the open-source computational fluid dynamics (CFD) toolbox OpenFOAM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…13. The same order of magnitude in this over-prediction of total effective viscosities is also reported [16]. In contrast to the experimental data, the DDES results predicts the fluctuation peak slightly farther downstream.…”
Section: First-and Second-moment Wake Statisticssupporting
confidence: 76%
See 3 more Smart Citations
“…13. The same order of magnitude in this over-prediction of total effective viscosities is also reported [16]. In contrast to the experimental data, the DDES results predicts the fluctuation peak slightly farther downstream.…”
Section: First-and Second-moment Wake Statisticssupporting
confidence: 76%
“…At higher Reynolds numbers ( > 1.0 × 10 4 ), the wake shed by a bluff body can be described by several characteristic quantities. Benchmark conditions [8,[16][17][18][19][20][21] at = 21 400 showed that the time-averaged drag coefficient ranges approximately 2.1 to 2.4, with Strouhal numbers ranging 0.12 to 1.4. This shedding frequency is correlated to the vortex shedding pair that forms due to the roll-up of the shear-layer instabilities at the leading edges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Active and passive flow control methods were studied to improve the intake performance. Finally, the article by Boudreau et al [13] investigates the use of large eddy simulations in predicting the flow behind a square cylinder at a Reynolds number of 21,400.…”
mentioning
confidence: 99%